Analysis of The "Sijagaron" Symbol in the Saur Matua Traditional Ceremony of the Batak Toba Tribe - Gloriana Sitompul (Asian Journal of Applied Education (AJAE), 2024)
This research aims to analyze the "Sijagaron" symbol in the Saur Matua traditional ceremony of the Toba Batak tribe, a cultural practice that illustrates the death of someone who has reached old age and has children. Saur Matua, which means "blessed" in the Batak Toba language, is the highest form of respect for people who die after completing a successful life and having many descendants. The Sijagaron symbol, in the form of a series of plants such as banyan plants, silinjuang leaves, and sanggar flowers, is placed on the coffin as a sign of honor and achievement. This research examines the philosophical and cultural meaning of Sijagaron, as well as its role in traditional rituals that show prosperity and success in a person's life. Through a qualitative approach and in-depth analysis, this research explores how Sijagaron symbolizes the relationship between humans, nature and God in Toba Batak culture. The research results are expected to provide insight into the cultural values ​​contained in the Sijagaron symbol and the importance of the Saur Matua ceremony in Toba Batak society, as well as its contribution to understanding cultural heritage and customs.